'In This Interregnum': Dialectical Themes in the Critique of Criminal Justice. (December 2017) - Carvalho, Henrique; Norrie, Alan
In this article, we offer a critical examination of the long and rich history of criminal justice scholarship in the pages of Social and Legal Studies. We do so by identifying and exploring a dialectical tension in such scholarship, between the recognition of the role of criminal justice as an instrument of violence, exclusion and control on the one hand and the effort to seek, through or perhaps beyond the critique of criminal justice, an emancipatory project. We explore this tension by examining four areas in scholarship: popular justice, social control and governmentality, gender and sexuality and transitional justice. Relating forms of critique to the historical development of a unipolar political world order from the time of the journal's inception, we argue that the criminal justice scholarship in Social and Legal Studies positions it, like the world it describes, in a sort of 'interregnum'. This is a place where the tension between the two poles of emancipation and control is evident but shows few signs of resolution. Each of the four themes displays a different critical perspective, one that reflects a different response to living in a world where legal, social and political emancipation struggles against the weight and direction of history. Critique nonetheless reflects on criminal justice to reaffirm the need for emancipatory change and consider how it may be achieved.